Reproductive health in Turner’s syndrome: from puberty to pregnancy - Porcu, Eleonora; Cipriani, Linda; Damiano, Giuseppe (Frontiers in Endocrinology, 2023)
Turner syndrome (TS) is a genetic pathology that affects about 1/2500 newborn females. Turner's syndrome is characterized by highly variable genetic anomalies that consist in a partial or complete deletion of the X sexual chromosome; it can be present as a monosomy or as a mosaicism with two o three different cellular lines. 50% of the patients with Turner's syndrome has a 45 XO karyotype while the remaining cases have karyotypes with mosaicism or X isochromosome or with partial or whole Y chromosome. This pathology is characterized by multiple anomalies that involve physical and cognitive development and in particular endocrine, cardiovascular, reproductive, auditive and visual systems. Integrity of the X chromosome in essential for fertility. In TS is accelerated germ cells apoptosis. About 30% of TS girls have some pubertal development, 10-20% undergo menarche and 2-8% go through spontaneous pregnancy. Women with TS should be informed about the risk of premature menopause and should be referred, if possible, to a specialist evaluation with a doctor expert in assisted reproductive techniques. In adolescents and in adults, Premature Ovarian Insufficiency (POI) can be evaluated clinically and biochemically with the classic combination of amenorrhea and elevated FSH concentrations (hypergonadotropic hypogonadism). However, in postpubertal adolescents and adult women, reproductive hormones may remain within the normal range before POI is clinically evident, despite significant depletion of the ovarian reserve. Today, reproductive medicine offers the opportunity of fertility preservation in women with premature ovarian insufficiency (POI). Two techniques have been suggested such as ovarian cortex cryopreservation and oocytes cryopreservation.